7I-Model for Smart City Development - Popov, Evgeny; Semyachkov, Konstantin (Archives of Business Research, 2020)
The subject of the study is the development of smart cities, the effectiveness of the socio-economic systems of which is ensured by the introduction of advanced digital technologies. The research method is a logical system analysis of previous studies highlighting the development priorities of smart cities and attracting authors' results on institutional modeling of economic activity. The purpose of the study is to develop a system of sequential priorities for the development of smart cities based on institutional modeling of the stages of the formation of a digital society. As a result of the study, the author’s model of smart city development priorities is presented (the “7I” model), it is shown that the basis for the development of smart cities is the following stages: engineering infrastructure, institutes, communication and communication systems, data integration, user and technical systems interaction, innovations, application of innovation in the components of a smart city. It was determined that these stages of the development of smart cities are based on the use of advanced digital technologies and their applications: big data processing, the use of cloud technologies, digital platforms, blockchain technology, as well as shared economy, crowdsourcing, Internet of things, etc. It is concluded that the development of smart cities corresponds to the national interests of states in the formation of a digital society and ensures the safety of life in the context of the application of digital technologies.